1999
DOI: 10.1046/j.1439-0523.1999.00388.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation of resistance to Pseudocercosporella herpotrichoides (Fron) Deighton in wheat genotypes carrying the gene Pch‐1

Abstract: The effect of the gene Pch‐1 on the resistance of wheat to Pseudocercosporella herpotrichoides was studied at four growth stages. The germplasm used consisted of adapted cultivars, genotypes provided by European plant breeders, near‐homozygous lines and double haploid lines developed from our own breeding projects. The resistance was measured by ELISA. At all growth stages, genotypes carrying Pch‐1 differed significantly in resistance. At early growth stages, there was a strong effect of the gene in most genot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 11 publications
0
26
0
Order By: Relevance
“…ventricosa segment in which the linkage has been broken, or to another genetic source that promotes yield potential. Previous reports Lind 1999) have shown that cultivars carrying Pch1 with Cappelle Desprez (Pch2 and Q.Pch.jic-5A) in their pedigrees, such as Rendezvous, have enhanced adult plant resistance. However, those varieties are not widely used in breeding as a result of their relatively low yield in spite of the absence of the disease.…”
mentioning
confidence: 99%
“…ventricosa segment in which the linkage has been broken, or to another genetic source that promotes yield potential. Previous reports Lind 1999) have shown that cultivars carrying Pch1 with Cappelle Desprez (Pch2 and Q.Pch.jic-5A) in their pedigrees, such as Rendezvous, have enhanced adult plant resistance. However, those varieties are not widely used in breeding as a result of their relatively low yield in spite of the absence of the disease.…”
mentioning
confidence: 99%
“…Renan possesses powdery mildew resistance gene Pm4b. It also has Pch1 for eyespot resistance (Lind 1999). Resistance to Fusarium head blight was described by Bai and Shaner (2004) and observed also by Chrpová (personal communication).…”
Section: Discussionmentioning
confidence: 77%
“…1994), relative rates of O. yallundae and O. acuformis development in wheat (Poupard et al. 1994), variation in eyespot response in Pch1 ‐carrying genotypes (Lind 1999) and quantitative inheritance of eyespot resistance in diallel crosses (Lind 2000).…”
Section: Methods For the Assessment Of Eyespot Resistancementioning
confidence: 99%